Pretneria metkae mirae ssp. n. (Coleoptera: Cholevidae) from mount Prisojnik, Slovenia - Bognolo, Marco (Acta entomologica slovenica (Ljubljana), 2001)
Pretneria metkae mirae ssp. n. is described from Prisankova Jama, on Mount Prisojnik (Slovenia). The affinity with Pretneria metkae Bognolo from Mount Triglav is discussed, as well as the relationships between the distribution and the geological features of the habitats.
Keywords: Coleoptera; hrošči; Slovenia; Slovenija